Effects of step-deposition on structures and properties of transparent conducting aluminum-doped zinc oxide films prepared by DC magnetron sputtering - Tohsophon T. (2014)
The 2 wt% aluminum-doped zinc oxide films (AZO) was sputtered on corning glass plate at temperatures of 30-200 °C by DC magnetron sputtering using ceramic target. The microstructures and electrical resistivity of thin films were investigated by scanning electron microscope (SEM) and the van der Pauw method. The optical transmittances of films were measured by UV visible spectrophotometer in the wavelength of 300-900 nm. It was found that the average optical transmittances of specimens were 88%. Highly oriented AZO films in the (0 0 2) direction was observed in specimens as increasing of the substrate temperature. The dense film increased as the temperature increases. In addition, craters of greater depth with more compactness were obtained by step-deposition. The lowest resistivity of 9×10-4 Ω cm with film thickness of 700 nm was found in specimen grown by step-deposition at 200 °C. © 2006 Elsevier B.V. All rights reserved.